Gerbera jamesonii production in the São Francisco Submédio Valley (Research, Society and Development, 2020)
Gerbera cultivation in the northeastern region of Brazil is still incipient, but it can be an alternative to crop diversification. The use of irrigation strategies can mitigate competition for available water, especially during water crisis. The objective of this study was to evaluate the production and quality of the inflorescences of gerberas as a function of water applied in the São Francisco Submédio Valley. This work was conducted in Juazeiro-BA, in a randomized block design, with 2 × 4 subdivided plots. The main plots consisted of two gerbera hybrids (Essandre and DTCS), and the subplots were composed of four areas established at 60%, 80%, 100%, and 120% of the crop evapotranspiration (ET), in five replications. ET was determined by weighing lysimeter, in a 240-day cycle after acclimatization. The number, length, diameter, and longevity of the stems were quantified. Means were compared using Tukey’s test at 5% significance level, and regression analysis was performed on the subplot ET factor. The severe deficit made commercial production of cutting gerbera unfeasible. The DTCS hybrid showed higher production and quality of the flowers; however, there was a reduction in the length of the stem and the longevity of the inflorescence compared to Essandre, due to the differentiation of the ET areas. The 20% water deficit may be a positive approach to water management in the face of water scarcity, but it can result in a 13% loss of the commercial production, and a 12.4% reduction in the quality of the stems. The water-saving strategy for gerbera crop requires economic analysis.